Subsidies and innovation in the recent financial crisis - Marek Giebel; Kornelius Kraft (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We analyze the impact of subsidies on R&D expenditures in the financial crisis and beyond. The financial crisis has led to considerable turmoil in financing and, as a result, to restrictions of firms' access to external financing. Utilizing this fact, we identify and analyze financing constraints in two ways. First, firm financing constraints are determined via their credit rating and second, restrictions from the supply side are identified via the firm's main banks capital reserves. The results of our empirical test imply that R&D investments of non-subsidized firms decrease during the crisis. This effect is particularly pronounced for firms that are affected by financing constraints on the firm or bank side. Finally, our results imply that subsidies can at least partially compensate for these negative effects.
Keywords: G01; G21; G24; G30; O16; O30; O31; O32; 330; R&D investment; financing constraints; financial crisis; R&D subsidies